Efectos de un plan de prevención sobre autoimagen en un deportista masculino que presente signos de alarma de vigorexia (2024)
Currently, the term "vigorexia" refers to a condition that has emerged in recent times, characterized by a distortion of body image that negatively affects the lives of those who experience it. It is marked by an excessive concern over one or more perceived flaws in physical appearance. The general objective of this research is to analyze the effects of a prevention plan on the self-image of a male athlete aged between 20 and 40 years who exhibits warning signs of vigorexia.